Raise the Bar and Lower the Dose: Current and Future Strategies for Radiation Dose Reduction in Head and Neck Imaging - Ibrahim, M.; Parmar, H.; Christodoulou, E.; Mukherji, S. (American Journal of Neuroradiology, 2014)
SUMMARY: Technologic advances in CT have generated a dramatic increase in the number of CT studies, with a resultant increase in the radiation dose related to CT scanning. Such increase in radiation dose is becoming a concern for the radiology community, especially with increasing public awareness of the dose burden related to examinations. To cope with the increase in CT-related radiation exposure, it is becoming necessary to optimize CT imaging protocols and apply radiation dose reduction techniques to ensure the best imaging with the lowest radiation dose. ASIRadaptive statistical iterative reconstruction algorithmATCMautomated tube current modulationCTDICT dose indexDLPdose-length productFBPfiltered back-projection